Preparation Methods, Interactions and Functional Properties of Starch-Macromolecule Complexes: A Review - LAI Haibin, GAO Jing (Shipin Kexue)
The stability and bioavailability of biomacromolecules are enhanced when they are encapsulated with starch, and this in turn alters functional characteristics of starch. As a result, effective combination of starch with macromolecules holds vast potential for applications in delivery systems and functional foods. However, different types of starch, the differences in properties among macromolecules and different preparation methods result in notable variations in interaction and functional characteristics among starch-macromolecule complexes. This review summarizes the preparation techniques, interactions, and functional characteristics of binary and ternary complexes of starch and macromolecules. This article aims to contribute to a deep understanding of the nutritional value, sensory characteristics, and functional characteristics of novel starch-based complexes in order to expand their applications in various fields such as functional foods, biotechnology, and pharmaceuticals.